Automated Multi-document Summarization in NeATS - Lin, Chin-Yew; Hovy, Eduard (The second international conference on Human Language Technology Research (HLT 2002), 2002)
This paper describes the multi-document text summarization system NeATS. Using a simple algorithm, NeATS was among the top two performers of the DUC-01 evaluation.